A CONFIRMATORY FACTOR ANALYSIS OF THE MEASURE OF PHYSICAL AND PSYCHOLOGICAL STATES FOR SPORT INJURY IN THAI ATHLETES - Bhasavanija, Tirata (Academic Journal of Thailand National Sports University, 2020)
The aim of current study was to examine the components of the physical and psychological states for sport injury in Thai athletes by using the confirmatory factor analysis. Participants were 157 Thai athletes who got sport injured (male = 94, female = 63). 71.3 percent of them aged between 18 – 21 years old, from 21 kinds of sport. Purposive sampling was used to particularly select the sport injured athletes to participate in this study. Equipment used in this study were 1) the imagery of emptiness state (used during respond to Item 15 and 18), and 2) the Measure of Physical and Psychological States for Sport Injury (MPPSSI). The Intraclass Correlation Cronbach’s Alpha reliability value was 0.875 and the apart-7-day test-retest reliability value was 0.751 analysed by using the Pearson’s Product Moment Correlation Coefficient. This measure was developed from the Measure of Physical and Psychological States in Sports: MPPSS, Bhasavanija, Cherathammawat, Chobthamasakul, & Poompin, 2015), consisting of five components and 18 sub-scales: quality of life, confidence, anxiety, perception of pain, and perception of muscle tension. Results were that the confirmatory factor analysis of five factors loading the physical and physical states for sport injury (Quality of Life, Confidence, Anxiety, Perception of Pain, and Perception of Muscle Tension) which were proposed could be confirmed that the proposed model was an underlying 18-subscale structure (Chi – Square = 61.96, df = 97, p = 0.99, RMSEA = 0.00, GFI = 0.96, AGFI = 0.93). This study suggested that 5-factor model has close relation and can be used for measuring the physical and psychological states in the injured athlete together with medical treatment.